1970
DOI: 10.1002/1097-0142(197008)26:2<436::aid-cncr2820260227>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

A study of environmental influence upon salivary gland neoplasia in rats

Abstract: An animal model system was used in an attempt to explore suspect relationships between 3 groups of possible carcinogenic co‐factors (nutritional, endocrine, and thermal) and the seemingly high salivary gland cancer experience of Arcticdwelling Eskimos. Two hundred and thirty weanling Sprague‐Dawley rats were randomized into 7 groups to study effects of vitamin A deficiency, hypercortisonism, hyperthyroidism, hypercortisonism plus hyperthyroidism combined, and a windy, cold, humid environment upon submaxillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
1996
1996

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The DMBA-induced SMSG tumor model is well established (18)(19)(20) and has a distinct advantage in that the DMBA-injected experimental gland and the vehicle-injected contralateral control gland are in the same animal. This reduces variability caused by factors such as differences among rats in food intakes and physiological states.…”
Section: Discussionmentioning
confidence: 99%
“…The DMBA-induced SMSG tumor model is well established (18)(19)(20) and has a distinct advantage in that the DMBA-injected experimental gland and the vehicle-injected contralateral control gland are in the same animal. This reduces variability caused by factors such as differences among rats in food intakes and physiological states.…”
Section: Discussionmentioning
confidence: 99%
“…Etid poitit: 16 weeks was selected as the termination date because Shafer (1962), Glucksmann & Cherry (1966), Rowe et al (1970) have shown that a significant percentage of animals treated with DMBA bear carcinomas by 16 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…As in other epithelia, squamous metaplasia with keratin production by ductal cells was demonstrated (HAYES, MCCOMBS and FAHERTY, 1970;PARNELL and SHERMAN, 1962;TROWBRIDGE, 1969). Also in vitamin A deficiency, potentiation of chemically induced salivary gland neoplasia has been described (ROWE et al, 1970). What effect excess vitamin A might have on cells of salivary gland tissue has not been reported.…”
Section: Introductionmentioning
confidence: 97%